Drug interactions in COVID-19 treatment. Systematic review - Arkadiusz Adamiszak; Tomasz Torliński; Edmund Grześkowiak; Alicja Bartkowska-Śniatkowska; Agnieszka Bienert (Polish Pharmaceutical Society, 2022)
The COVID-19 pandemic has driven the experimental, off-label treatments with co-administration of supportive therapies for many patients with severe infections and coexisting chronic conditions. This situation has inevitably led to polypharmacy, which is always related to a disproportionately large increase in drug-drug interaction and adverse drug effects probability. Immediate, difficult therapeutic decisions have taken priority, rendering drug interactions and adverse drug effects less important. Additionally, there has been a shortage of studies describing such interactions and guiding how to avoid them in clinical practice. Our systematic review aimed to analyze and summarize the available information about clinically relevant drug-drug interactions observed between COVID-19 treatment and other drugs used in the care of individual patients. To perform a systematic review, we searched PubMed and Embase databases. After data extraction, we checked drug-drug interactions with two independent interaction checkers: the COVID-19 Drug Interactions checker created by the University of Liverpool and the Drug Interactions Checker, powered by the American Society of Health-System Pharmacists, Cerner Multum, and IBM Watson Micromedex. According to our findings, chloroquine or hydroxychloroquine and lopinavir/ritonavir as a COVID-19 treatment carried the highest risk of interactions related to QT prolongation and cytochrome P450 inhibition. The other group most at risk of interactions involved patients taking immunosuppressants with the potential to prolong the QT interval and direct oral anticoagulants. In the case of immunosuppression therapy, one should expect increased blood levels of drugs and a higher risk of toxicity, co-administration of QT prolongation drugs involves the risk of life-threatening arrhythmias, and anticoagulant treatment requires paying attention to the increased risk of bleeding. Considering complex COVID-19 therapy, avoiding drug-drug interactions requires a multidisciplinary approach and up-to-date information about possible interactions.